Diversity of Predatory Arthropods on Sweet Corn (Zea Mays L. Saccharata Sturt) in Telagawaru West Lombok - Utomo, Sandrina Mayreva; Haryanto, Hery; Nikmatullah, Aluh (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Sweet corn (Zea mays L. saccharata Sturt) is an important crop in Indonesia but remains vulnerable to pest attacks that lower its productivity. Excessive reliance on chemical pesticides raises environmental and resistance concerns. This study aims to explore the diversity of predatory insects as natural enemies of pests in sweet corn fields in Telagawaru Village, Labuapi Sub-district, West Lombok. The research was conducted from November 2024 to January 2025 in two cultivation sites. A descriptive method using field surveys and laboratory identification was applied. Observations were carried out using purposive sampling within five 5×5 m blocks per field, at five intervals between 30–50 days after planting. Pitfall and yellow pan traps were used for 24-hour sampling. Data were analyzed using Shannon-Wiener diversity index (H'), evenness index (E), and dominance index (D). Results revealed 1,234 predator individuals from five orders, 19 families, and 31 genera. H’ was 1.909 (moderate), E was 0.2327 (low), and D was 0.2129 (low). It can be concluded that sweet corn fields in the study area have moderate predator diversity with low dominance. Further long-term monitoring is recommended to support ecological pest control strategies by understanding predator dynamics across environmental and agricultural factors.